2017
DOI: 10.1007/978-3-319-56017-5_22
|View full text |Cite
|
Sign up to set email alerts
|

UV Disinfection of Wastewater and Combined Sewer Overflows

Abstract: Municipal wastewater contains bacteria, viruses, and other pathogens that adversely affect the environment, human health, and economic activity. One way to mitigate these effects is a final disinfection step using ultraviolet light (UVL). The advantages of UVL disinfection, when compared to the more traditional chlorine, include no chlorinated by-products, no chemical residual, and relatively compact size. The design of most UV reactors is complex. It involves lamp selection, power supply design, optics, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…The advantages of UV disinfection compared to the chemical agents, include no by-products, no chemical residual, and relatively compact size. However, the level of disinfection that can be achieved is often limited by particle-associated organisms in CSO water and the UV transmittance of CSOs can be as low as 30% and the TSS can reach 200 mg/l (Gibson et al, 2017); hence, the use of a pretreatment unit is utmost important to increase disinfection efficiency. Two pilot-scale disinfection units comprised of ozone and UV were tested by (Tondera et al, 2015) on CSOs; where the ozone was found to be more effective than UV (ozone: 3.1-3.4 log, UV: 1.7-2.2 log) on the reduction of E. coli, coliform bacteria and intestinal enterococci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of UV disinfection compared to the chemical agents, include no by-products, no chemical residual, and relatively compact size. However, the level of disinfection that can be achieved is often limited by particle-associated organisms in CSO water and the UV transmittance of CSOs can be as low as 30% and the TSS can reach 200 mg/l (Gibson et al, 2017); hence, the use of a pretreatment unit is utmost important to increase disinfection efficiency. Two pilot-scale disinfection units comprised of ozone and UV were tested by (Tondera et al, 2015) on CSOs; where the ozone was found to be more effective than UV (ozone: 3.1-3.4 log, UV: 1.7-2.2 log) on the reduction of E. coli, coliform bacteria and intestinal enterococci.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the bathing water quality can be maintained by instant disinfection of inflowing CSO water (Chhetri et al, 2016). To date, various disinfection methods at lab-and/or pilot-scale were proposed for the removal of pathogens from CSOs, such as peracetic acid (Chhetri et al, 2016), performic acid (Chhetri et al, 2014;Tondera et al, 2016), hypochlorite (McFadden et al, 2017), ozone (Tondera et al, 2015) and UV (Gibson et al, 2017(Gibson et al, , 2016. However, the applicability and frequency of a disinfection method applied for CSOs are often site-specific due to high variability of the pollution load in CSOs and therefore need optimization to assess the effectiveness of the chosen disinfectant agent.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, para que la luz UV pueda ejercer efectos desinfectantes es necesario que la longitud de onda sea absorbida con la finalidad de generar alteraciones en los ácidos nucleicos, como la formación de dímeros de pirimidina, para la interrupción de procesos como la replicación celular en los microorganismos contaminantes. Con base en lo anterior, es necesaria la implementación de reactores de pre tratamiento de luz UV que permitan maximizar la exposición del agua a la radiación y evitar problemas asociados con compuestos que absorban la luz y disminuyan su capacidad de desinfección 23 . Con respecto a los tratamientos químicos, las máximas concentraciones empleadas en este estudio no lograron eliminar por completo la carga bacteriana, a pesar de presentar disminuciones de UFC significativas, en comparación con el agua sin pre tratar.…”
Section: Discussionunclassified
“…Otro tipo de tratamientos químicos, como el uso de 5 M NaOH junto con 5 M HCl son capaces de disminuir una elevada carga bacteriana hasta valores de 100 UFC/mL 27 . A pesar de esto, en general, los métodos de desinfección químicos suelen tener como una mayor desventaja frente a la luz UV la presencia de cloro o sustancias químicas residuales o la necesidad de aplicar tratamientos posteriores a la desinfección del agua empleada 23,28 . En el caso del CH₃CO₃H, no se presentan compuestos tóxicos o mutagénicos residuales en el agua pretratada, lo cual constituye una ventaja sobre los procesos de cloración.…”
Section: Discussionunclassified
“…Aerosol containing HCoV under different UV wavelengths showed that doses required to inactivate the virus ranged between 1.2 - 1.7 J/m 2 [18] . Even though particular studies have not been done directly with wastewater, known technologies can generate dosages between 1-200 J/m 2 and could be easily modified to dose sufficient UV especially at 254 nm as long as the transmission of UV to the wastewater considered the turbidity and UV transmittance for succesfull virus elimination [45] . The advantage of employing UV for wastewater treatment for SARS-CoV-2 is the absence of residues resulting in toxic byproducts.…”
Section: Managing Sars-cov-2 In Wastewater and Sewage Systemsmentioning
confidence: 99%